A systematic review and meta‐analysis of nutrition interventions for chronic noncancer pain. Issue 2 (7th October 2018) - Brain, K.; Burrows, T. L.; Rollo, M. E.; Chai, L. K.; Clarke, E. D.; Hayes, C.; Hodson, F. J.; Collins, C. E.
Abstract: Background: This systematic review aimed to evaluate the impact of nutrition interventions on participant reported pain severity and intensity in populations with chronic pain. Methods: Eight databases were systematically searched for studies that included adult populations with a chronic pain condition, a nutrition intervention and a measure of pain. Where possible, data were pooled using meta‐analysis. Seventy‐one studies were included, with 23 being eligible for meta‐analysis. Results: Studies were categorised into four groups: (i) altered overall diet with 12 of 16 studies finding a significant reduction in participant reported pain; (ii) altered specific nutrients with two of five studies reporting a significant reduction in participant reported pain; (iii) supplement‐based interventions with 11 of 46 studies showing a significant reduction in pain; and (iv) fasting therapy with one of four studies reporting a significant reduction in pain. The meta‐analysis found that, overall, nutrition interventions had a significant effect on pain reduction with studies testing an altered overall diet or just one nutrient having the greatest effect. Conclusions: This review highlights the importance and effectiveness of nutrition interventions for people who experience chronic pain.